(3GdahGFO GdRjfjI GdedJbWI ef GdaQGFO GdMSfjIs - (3GdeUQj GdMfaj, GHf fLje, Rjf GdOjf Hf EHQGgje Hf eMeO, (B970 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdgGOj Edi Gdabg aj GdOjf hHYO aEfj bO LeYJ ahGFO cKjQI ef GdaQhY GdabgjI hSejJg ahGFO RjfjI aj ePgH GdMfajIs
(3BNQgG (B:s
(3HYO GdGLGQI aj GdeSJCLQ GdChdi aGdKGfjI aJM GdChdi ceG aj GdHRGRjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 64s
(3eYLe GdeDdajf (B1 / 740s
(3cTa GdXfhf (B2 / 1297s
(3TPQGJ GdPgH (B8 / 358s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs